Independent bodies’ oversight of the non-governmental sector in Iraq - Hamdi , Omar (Journal of Legal Sciences, 2025)
Following the change of the system of government from presidential to parliamentary under the 2005 Constitution, the legal system in Iraq faced the emergence of independent oversight bodies that were not known before the entry into force of this Constitution, and which exercise oversight powers mainly over some government agencies. However, this did not prevent the extension of the control of some of these bodies to other agencies not affiliated with the government, even if they participate with government agencies in satisfying some public needs, aiming to achieve the public interest despite their private, not public, ownership, such as private universities and private banks. In light of these objectives, independent bodies are permitted to extend their oversight over these non-governmental bodies, given that they are governed by the state’s general policy. It is also necessary to ensure that oversight bodies do not abuse the rights of non-governmental bodies whose goal is to achieve public benefit, not merely material gain. Institutional coordination between independent bodies and state bodies that exercise oversight powers is essential to prevent duplication between them.